Characterizing worry content and impact in pregnant and postpartum women with anxiety disorders during COVID‐19. (4th January 2022) - Green, Sheryl M.; Furtado, Melissa; Inness, Briar E.; Frey, Benicio N.; McCabe, Randi E.
Abstract: The novel COVID pandemic has had a substantial impact on global mental health, including those populations that are inherently vulnerable such as pregnant and postpartum (perinatal) women. Anxiety disorders (ADs) are the most common mental health disorders during the perinatal period, affecting up to one in five women. However, since the onset of the pandemic, up to 60% of perinatal women are experiencing moderate to severe levels of anxiety. Given the substantial increase in perinatal anxiety during COVID, we sought to better understand its phenomenology by characterizing the collective worry content and impact of COVID using a content analysis. Eighty‐four treatment‐seeking pregnant ( n = 35) and postpartum ( n = 49) women with a principal AD, participated in this study between April and October 2020. In addition to completing questionnaire measures and a semistructured diagnostic interview, participants were asked to (1) describe their top excessive and uncontrollable worries, (2) describe additional COVID and non‐COVID worries, and (3) describe how the pandemic had affected their lives. All responses were given verbally and transcribed verbatim by assessors. A content analysis led to the emergence of various COVID and non‐COVID worry and impact themes. One third of participant's principal worries were specific to COVID, and 40% of COVID worries were specific to the perinatal context. Understanding the worry content and impact of COVID may improve symptom detection and inform the development of targeted treatment strategies to support the mental health needs of perinatal women with ADs throughout the pandemic and thereafter. Understanding pandemic‐specific worries is important for perinatal symptom screening and may allow for the development of targeted treatment strategies to address COVID‐specific worries and impact.